4-Phenylbutyrate protects against rifampin-induced liver injury via regulating MRP2 ubiquitination through inhibiting endoplasmic reticulum stress. Issue 2 (1st February 2022) - Chen, Jing; Wu, Hongbo; Tang, Xudong; Chen, Lei
ABSTRACT: Rifampin (RFP), a first-line anti-tuberculosis drug, often induces cholestatic liver injury and hyperbilirubinemia which limits its clinical use. Multidrug resistance-associated protein 2 (MRP2) localizes to the hepatocyte apical membrane and plays a pivotal role in the biliary excretion of bilirubin glucuronides. RFP is discovered to reduce MRP2 expression in liver cells. 4-Phenylbutyrate (4-PBA), a drug used to treat ornithine transcarbamylase deficiency (DILI), is reported to alleviate RFP-induced liver cell injury. However, the underlying mechanism still remains unclear. In the current study, we discovered that RFP induced HepG2 cell viability reduction, apoptosis and MRP2 ubiquitination degradation. Administration of 4-PBA alleviated the effect of RFP on HepG2 cell viability reduction, apoptosis and MRP2 ubiquitination degradation. In mechanism, 4-PBA suppressed RPF-caused intracellular Ca 2+ disorder and endoplasmic reticulum (ER) stress, as well as the increases of Clathrin and adapter protein 2 (AP2). ER stress marker protein C/EBP homologous protein took part in the modulation of AP2 and clathrin. Besides, 4-PBA reduced the serum bilirubin level in RFP-induced cholestasis mouse model, along with raised the MRP2 expression in liver tissues. These findings indicated that 4-PBA could alleviate RFP-induced cholestatic liver injury and thereby decreased serum total bilirubin concentration via inhibiting ER stress and ubiquitination degradation of MRP2, which provides new insights into the mechanism of 4-PBA in the treatment of RFP-induced cholestasis and liver damage. Graphical abstract: uf0001